(untitled) (Biocenosis, 2022)
Education for Sustainable Development (ESD) has been integrated into numerous global frameworks and conventions. Currently, there is growing international recognition that considers ESD as an integral element of quality education, since it provides people with skills that allow them to face the challenges posed by changes regarding environmental- alteration, which in turn manifest themselves as social fractures. In this sense, the Education policy and action plan for Sustainable Development, approved by the Higher Council of Education in 2020, formalize the route for the implementation of such a model as an axis that can permeate the curriculum of the different subjects in the public school system, and in response to the commitment acquired by the country for sustainable development achievement goals (SDGs.)